2021
DOI: 10.3390/agronomy11030509
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of Digestates and Combinations of Digestates and Fertilizer on Yield and Nutrient Use of Brassica juncea (Kai Choy)

Abstract: Anaerobic digestion of organic wastes produces solid residues known as digestates, which have potential as a fertilizer and soil amendment. The majority of research on digestate focuses on their fertilizer value. However, there is a lack of information about additional effects they may have on plant growth, both positive and negative. Understanding the effects of digestate on plant growth is essential to optimizing their use in agriculture and helping close the loop of material and energy balances. This greenh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Chantigny et al [ 27 ] also reported that digestate application produced higher yields as the necessary nutrients needed for growth and yield were provided for plant uptake and soil fertility. Longer-term digestate application ranging from three to six years also resulted into higher yields in other studies [ 1 , 13 , 27 , 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Chantigny et al [ 27 ] also reported that digestate application produced higher yields as the necessary nutrients needed for growth and yield were provided for plant uptake and soil fertility. Longer-term digestate application ranging from three to six years also resulted into higher yields in other studies [ 1 , 13 , 27 , 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 58%
“…The contribution of digestate to the N availability in the soil presents an important argument for their application. Digestate is particularly rich in ammonium nitrogen (NH 4 -N), a form of N that is readily available for uptake by plants [ 13 ]. The ratio of the mineral N fraction to the total N content is an important indicator of its impact on the N cycle and transformation in soil during plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…BGS enriched with variable doses of NPK promotes growth and pod yield in the pea plant [ 124 ]. As compared to fertilizer control, Jamison et al [ 125 ] observed a slight increment in nutrient uptake and use efficiency in Brassica juncea using lignocellulosic biomass digestate supplemented with commercial liquid fertilizer. Do and Scherer [ 126 ] witnessed higher ryegrass yield using hygromull-enriched anaerobic digestate.…”
Section: Solutionsmentioning
confidence: 99%
“… Digestate combination with liquid fertilizer showed a slight increase in nutrient uptake, nutrient (nitrogen) use efficiency, and growth in Brassica juncea (Kai Choy) as compared to fertilizer control (100% fertilizer). Jamison et al [ 125 ] BGS (substrate feed rabbit manure) + biofertilizers [ A. chrococcum SARS 101+ AMF (spores of Glomus clarum , Gigaspora margarita , Glomus mosseae ) + B. circulans ARC-SWERI-2] + 50% NPK. Maximum leaf area (1238.2 cm 2 and 1147.7 cm 2 ), dry weight of root (17.11 g and 18.94 g), and leaves (44.85 g and 45.59 g) in maize during both the growing seasons.…”
Section: Solutionsmentioning
confidence: 99%
“…There are numerous reports from field and pot trials and the authors demonstrated the beneficial effects of digestate application to agricultural soil on crop yields [15,[30][31][32][33][34][35][36][37][38][39][40][41][42]. It is outlined that the desirable effects of the agricultural utilization of digestate can be achieved, i.e., complete avoidance of fertilizers' usage due to the presence of easily available forms of the most important biogenic nutrients-nitrogen and phosphorous, which has a desirable environmental impact.…”
Section: Introductionmentioning
confidence: 99%